Description of a new species and new country distribution records of Bactrocera (Diptera: Tephritidae: Dacinae) from Cambodia - Leblanc, Luc; Jose, Michael San; Rubinoff, Daniel (Zootaxa, 2015)
Bactrocera (Bactrocera) kohkongiae Leblanc (Diptera: Tephritidae: Dacinae), from the Koh Kong Province of Cambodia, is described as new. This species belongs to the Oriental fruit fly (B. dorsalis) complex. Genetic sequences (mitochondrial COI and nuclear EF1α and Period) are deposited in GenBank. A haplotype network, based on the COI sequences for 21 specimens, shows high genetic diversity. New country records from Cambodia are included for 22 species.